The effect of gonadotropin-releasing hormone analog treatment (leuprolide) on body fat distribution in idiopathic central precocious puberty - Taşcilar, Mehmet Emre; Bilir, Pelin; Akinci, Ayşehan; Köse, Kenan; Akçora, Dilek; Inceoğlu, Deniz; Fitöz, Suat Omer (The Turkish Journal of Pediatrics, 2011)
Gonadotropin-releasing hormone analog (GnRHa) therapy is used in idiopathic central precocious puberty (ICPP) worldwide. It has also been shown that during this therapy, body mass index (BMI) increases slightly as a side effect. We investigated the side effects of GnRHa treatment in ICPP on body composition and insulin resistance (IR). Twenty girls (7.55 +/- 1.02 y) with ICPP were treated with GnRHa (leuprolide) for an average of 20.83 +/- 4.8 months. Bioelectrical Impedance Analysis (BIA) was used to measure the body's fat balance. Nine patients out of 20 (45%) had significant gain weight. We showed a significant elevation in trunk fat mass compare to baseline values (p < 0.01). These nine patients had high homeostasis model assessment (HOMA)-IR and low glucose/insulin (G/I) index. This study showed a slight increase in BMI, moderate increase in total body fat, and exaggerated elevation in trunk fat mass and IR in GnRHa-treated ICPP children.